2001
DOI: 10.1038/35051107
|View full text |Cite
|
Sign up to set email alerts
|

ICOS is critical for CD40-mediated antibody class switching

Abstract: The inducible co-stimulatory molecule (ICOS) is a CD28 homologue implicated in regulating T-cell differentiation. Because co-stimulatory signals are critical for regulating T-cell activation, an understanding of co-stimulatory signals may enable the design of rational therapies for immune-mediated diseases. According to the two-signal model for T-cell activation, T cells require an antigen-specific signal and a second, co-stimulatory, signal for optimal T-cell activation. The co-stimulatory signal promotes T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
448
3
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 596 publications
(479 citation statements)
references
References 22 publications
25
448
3
3
Order By: Relevance
“…The IL-10-secreting phenotype was stably maintained during T cell cloning, but secretion was, to a large extent, dependent on ICOS signaling, which is in agreement with previous reports [28][29][30][31]. Of note, studies in ICOS-deficient mice have revealed a key role for this costimulatory molecule in Tdependent B cell responses [24,25]. Together, these observations suggest that the ability of ICOS to support IL-10 production by T cells plays a critical role in the provision of help to B cells.…”
Section: Discussionsupporting
confidence: 91%
“…The IL-10-secreting phenotype was stably maintained during T cell cloning, but secretion was, to a large extent, dependent on ICOS signaling, which is in agreement with previous reports [28][29][30][31]. Of note, studies in ICOS-deficient mice have revealed a key role for this costimulatory molecule in Tdependent B cell responses [24,25]. Together, these observations suggest that the ability of ICOS to support IL-10 production by T cells plays a critical role in the provision of help to B cells.…”
Section: Discussionsupporting
confidence: 91%
“…ICOS has been considered an inducible T-cell costimulatory molecule important for CD40-mediated Ab class switching [30]; however, the recent studies of uncontrolled expression of ICOS in several gene-modified mice showing lupus-like pathology provide insight for the close relationship between ICOS-expressing CD4 1 T cells and autoimmunity [19,31]. In the present study, blockade of ICOS using neutralizing Ab significantly reduced the production of total IgG in RASV-administered MyD88 À/À mice, suggesting possible cross-talk between Tfh-like cells and B cells via ICOS-ICOSL interaction for hyper-IgG.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interactions between the different pathways and their interdependence on each other are only now becoming clear. This is especially true for the ICOS-B7RP1, B7-CD28/CTLA4 and CD40-CD154 pathways (26,27,34). For example, T-cell ICOS up-regulation is reduced in the absence of B7.1 and B7.2, but is restored following CD28 stimulation (26), whereas CTLA4 ligation blocks ICOS costimulation by preventing cell-surface expression and downstream second signals (27).…”
Section: Discussionmentioning
confidence: 99%